Social determinants of community-level human papillomavirus vaccination coverage in aschool-based vaccination programme. (12th January 2018) - Jean, Stephen; Elshafei, Malak; Buttenheim, Alison
Abstract : Objective: To assess social patterns in human papillomavirus (HPV) vaccine coverage in a school-based, government-funded vaccination programme located within a single-payer universal healthcare system. Design: We conducted a cross-sectional analysis of HPV vaccine uptake data for the 2013–2014 school year for 131 local authorities in England, and then evaluated the association between vaccine uptake and socioeconomic status at the aggregate level. Data sources: HPV vaccination coverage data from Public Health England's vaccine uptake guidance and the UK's March 2011 Census. Main outcome measures: We measured three-dose local authority-level vaccine series initiation to completion. Results: We found that in local authorities where there are more high-income families, the vaccination rate is lower than in local authorities with more low-income families. Local authorities with a higher percentage of whites, compared with non-whites, had higher HPV vaccination rates. Additionally, local authorities with more non-migrants had higher rates of vaccination. Local authorities with more education deprivation had higher rates of vaccination. Local authorities' higher proportions of high-status occupations had worse vaccination coverage. In bivariate analyses across all the socioeconomic indicators, a 1 SD change in the indicators was associated with about a 2.25 percentage point decrease (for income, education and occupation) or increase (for race and migrant composition) in HPV dose coverage in the local authority. In multivariable analyses, only race remained as a significant predictor of HPV coverage at the local authority level. Conclusions: Across all three doses, there are notable variations by socioeconomic status, with steep reverse gradients in three socioeconomic indicators. More quantitative and qualitative research needs to be conducted to determine the effects of the 2014 transition from a three-dose regimen to two-dose regimen on vaccination coverage, especially in groups that experience lower rates of vaccination.